Innovative Thinking and its Relation with the Cognitive Inhibition among at the University Students (Journal Of Educational and Psychological Researches, 2022)
This study aimed to measure the innovative thinking and cognitive cessation among university students. The sample consisted of (400) male and female students at al Mustansiriya University for the academic year (2018/2019). The results of the study showed that there are differences in innovative thinking and cognitive inhibition according to the gender variable in favor of males. There is a positive relationship between innovative thinking and cognitive inhibition. In light of these findings, the researcher presented a set of conclusions and recommendations.